Implementasi Pengelolaan Kebijakan Sarana dan Prasarana Di Raudhatul Athfal (RA) Perwanida 3 Tanjungsari Jogorogo Ngawi - Farihah, Elyaum (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2023)
Facilities and infrastructure are needed in school, without it, the school will not be effective and efficience. This research will examinies “Implementation of the Management Of Policy Facilitities and Infrastructure in Raudhatul Athfal (RA) Perwanida 3 Tanjungsari Jogorogo Ngawi”. Which aims to know the optimization of the management of facilities and infrastructure in Raudhatul Athfal Perwanida 3 Tanjungsari Jogorogo. Optimization the management of facilities and infrastructure done with seven stage, that is planning infrastructure, procurement infrastructure, the distribution of infrastructure. This research is a quality research descriptive, as an instrument main research focus to the principle and teachers of Raudhatul Athfal Perwanida 3 Tanjungsari. The method of data collection use the observation, interviews, and documentation while the data analysis using interactive analysis